Evaluation of Bioactivity and Preliminary Phytochemical Investigation of Herbal Plants Against Ampicillin Resistant Bacteria - Ainanshe Abdirahman; Rida Batool (Journal of Basic & Applied Sciences, 2016)
Presently, natural products are extensively used as substitute of synthetic drugs because of natural and environment friendly antimicrobial actions due to presence of bioactive compounds. These bioactive compounds are found extensively in herbs. In this study, bioactivity and phytochemical study of crude extracts of Ocimum basilicum, Thymus vulgaris, Rosmarinus officinalis and Origanum vulgare against ampicillin resistant bacterial strains isolated from fruits and vegetables eaten as raw, was investigated. Bacterial strains were isolated from the surface of selected washed fruits and vegetables by serial dilution method. Three morphologically different strains (A, P and L) were selected on the basis of resistance to ampicillin (150ug/ml). 16s rRNA sequencing revealed that bacterial strains A, P and L belong to Pseudomonas aeruginosa strain A, Pseudomonas aeruginosa strain P and Rhodobacter sphaeroides, respectively. Phytochemical screening showed presence of different chemical compounds such as alkaloids, tannins, saponins, phlobotannins, quinones, coumarin and flavonoids. Occurrence of saponins and flavonoids in the extract was further confirmed by thin layer chromatography (TLC). Ocimum basilicum, Rosmarinus officinalis and Origanum vulgare extracts caused inhibition of the isolated ampicillin resistant organisms (Pseudomonas aeruginosa) but effect of Thymus vulgaris was more pronounced. Anti-mitotic study revealed the ability of these extracts to reduce dividing cells by the anti-mitotic properties and this is helpful in inhibition of the development of cancer cells. Therefore, these plants can be used to discover natural products that will aid in more effective developments of new drug research activities.